HR IMPLICATIONS IN THE NEW NORMAL AND THE CHANGING WORK CULTURE DURING PANDAMIC TIMES OF COVID 19 (International Journal of Food and Nutritional Sciences, 2022)
In the recent times man is struggling with economy one side and the very survival of life on the other side. No one imagined ever that the entire world is going to be shaken by a virus called COVID 19 and no medicine, no vaccine and no lockdown could able to save the world during these days. In this scenario as a precautionary many confined themselves to home itself. Most of the organizations were closed their operations but some tried options like allowing employees work from home and get some revenue and also provide employment for at least some time. There were organizations which paid months together without any work and revenue but how long. This made some of the organizations to take a call on no work no pay. Unorganized labour travelled miles of journey by walk. There is no transport and restrictions everywhere. Govt. has planned a series of lock downs to contain the situation but when we will reach to the normal is uncertain. Mean while a new concept emerged called the new normal. This paper attempts to understand how the HR factor got influenced and what changes emerged in the work culture during the pandemic times.